Winter road - Butcher, Kristin, 1951- (Orca currents., 2022)
Kat is struggling with her dad's death, her mom's long hours with the family's trucking business, and her recent diabetes diagnosis. To spend more time with her mom on spring break, she stows away in her mother's semi-truck on a dangerous journey across a frozen lake nicknamed the Winter Road. However, the trek brings more adventure than Kat could have imagined.